Security of quantum position-verification limits Hamiltonian simulation via holography - Apel, Harriet; Cubitt, Toby; Hayden, Patrick; Kohler, Tamara; Pérez-García, David (The journal of high energy physics, 2024)
A bstract We investigate the link between quantum position-verification (QPV) and holography established in [ 1 ] using holographic quantum error correcting codes as toy models. By inserting the “temporal” scaling of the AdS metric by hand via the bulk Hamiltonian interaction strength, we recover a toy model with consistent causality structure. This leads to an interesting implication between two topics in quantum information: if position-based verification is secure against attacks with small entanglement then there are new fundamental lower bounds for resources required for one Hamiltonian to simulate another.